Transferable critical thinking skills of culinary and fashion students in educational practical activities at Vocational Schools - Komariah, Kokom; Rahmawati, Fitri; Asiatun, Kapti; Nurlita, Asri Andarini; Minarni, Maize Lina; Simaremare, Perawati (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
Efforts to continually develop the potential and skills of future teachers are crucial due to the increased demands placed upon them. This study aimed to examine the critical thinking abilities of students engaged in educational practice within vocational high schools, elucidating the challenges they encountered and proposing requisite strategies for surmounting them. Employing a quantitative descriptive approach, this research utilized surveys and focus group discussions (FGDs) as data collection instruments, validated through content validity measures. The study employe   ,;d students from the Department of Food and Clothing Education at the Faculty of Engineering, Universitas Negeri Yogyakarta, participating in Educational Practices within the Tourism Group Vocational High School, alongside tutor teachers guiding them. Analysis revealed that students exhibited commendable levels of critical thinking, evidenced by their adeptness in identifying information within the school environment, searching for information to analyze prevailing issues, and discerning various problems. Notably, the predominant obstacle impeding critical thinking proficiency was Sociocentrism, with a notable majority (61.64%) identifying unwarranted assumptions stemming from mass media sources (41.10%), and relativism due to deficient literacy skills, leading to closed-mindedness (31.51%).